Devon Women in Public and Professional Life, 1900-1950 Votes, Voices and Vocations - Neville, Julia (University of Exeter Press, 2021)
This book is one of the first to study the regional role of women in public and professional life, breaking new ground in early twentieth-century local and gender history. Covering politics (Eleanor Acland and Clara Daymond), medicine and education (Dr Mabel Ramsay and Jessie Headridge), and a variety of voluntary organizations (Florence Cecil, Georgiana Buller, Jane Clinton and Sylvia Calmady-Hamlyn), it shows how women worked individually and in collaboration to create new opportunities for women and girls in a large, mainly rural, county far from London and the industrial heartlands of England. These biographical studies are based on original research and reveal the huge public contribution made by these eight women, who up to now have been largely hidden from history. Devon Women in Public and Professional Life, 1900-1950 is a contribution to the history of women in Britain between the wars, a period that has received less attention than the Edwardian era and the two World Wars. It also fills a major gap in the history of Devon women, on which almost nothing has been published, and on Devon in the inter-war period, similarly neglected by historians. It will be of interest to academics and students in the fields of gender history and the history of modern Britain, as well as everyone interested in the history of twentieth-century Devon.